MATEC Web of Conferences - Kolomeytsev, A. A. specialist in the field of precision engineering Laboratory assistant of Tomsk Polytechnic University 1993- (2018)
This article describes the fluxgate magnetometer simulation in Comsol Multiphysics software package. The simulation results coincide with the experiment described earlier. Decomposition of the output signal by the Fourier coefficients shows a frequency doubling.